Bach - Grew, Eva; Grew, Sydney 1879- (New York Collier Books, 1962)
In the present book a picture is attempted of Bach's life and work, and of the conditions prevailing in the towns where he lived. Something, but not much at times, is said about the music he wrote in each place. Some particular attention has been paid to the cantatas, which are not well known, and to the organ works, which are well known, though in one section only, which is that of the compositions on free subjects. Both cantatas and organ works are dealt with chiefly as forms of music that are concerned largely with the use of chorales, this being a matter vital in the composer's art. - Preface.
The Bach family -- Eisenach (1685-95) -- Ohrdruf (1695-1700) -- Luneburg (1700-2/3) -- Weimar (1703) -- Arnstadt (1703-7) -- Muhlhausen (1707-8) -- Weimar (1708-17) -- Cothen (1717-23) -- Leipzig (1723-50) -- Bach's publications -- The "Catechism" preludes -- Organ music -- Further Clavier music at Leipzig -- The cantatas -- The B minor Mass and Magnificat -- The end -- Appendices. Calendar -- Catalogue of works -- Personalia -- Bibliography -- Genealogy of the Bach family.
"Catalogue of works": pages 224-237.
Originally part of the Master Musicians series published in the United States.
Includes bibliographical references (pages 242-244) and index.
Keywords: Bach, Johann Sebastian -- 1685-1750.